Normalizability analysis of the generalized quantum electrodynamics from the causal point of view - Bufalo, R.; Pimentel, B. M. [UNESP]; Soto, D. E. (World Scientific Publ Co Pte Ltd, 2017)
The causal perturbation theory is an axiomatic perturbative theory of the S-matrix. This formalism has as its essence the following axioms: causality, Lorentz invariance and asymptotic conditions. Any other property must be showed via the inductive method order-by-order and, of course, it depends on the particular physical model. In this work we shall study the normalizability of the generalized quantum electrodynamics in the framework of the causal approach. Furthermore, we analyze the implication of the gauge invariance onto the model and obtain the respective Ward-Takahashi-Fradkin identities.
Keywords: Axiomatic perturbative theory; generalized quantum electrodynamics; symmetry identities